Uses, constraints, and benefits of QRIS for merchants in Pondok Cina Station - Alyssa Tsabita Farhana; Dzahira Brilliant Syakira; Syukron, Muh; Ruth Meilianna; Purba, Yanti Astrelina (Jurnal Studi Komunikasi, 2025)
As technology continuously develops, economic activities begin to shift from the use of traditional payment systems to the use of digital payments. The urgency of the Micro, Small and Medium Enterprises (MSME) digitalisation program will gradually encourage small-scale street food vendors to adjust to technological advances. With this transformation, this study aimed to measure the development of QRIS usage among small merchants, whereby only little research has been done on the use of QRIS among small merchants. The researchers conducted a survey and in-depth interviews with small merchants at Pondok Cina Station, Depok, West Java, Indonesia. The results showed that there were more respondents who did not use QRIS with 53.3%, rather than those who used QRIS with 46,7%, although the difference was relatively not large. The biggest reason why merchants still do not use QRIS is that they do not understand how to use it and have encountered difficulty using it. In fact, there are still customers who rarely use it. Nevertheless, meeting high customer demand is one of the most common reasons why merchants use QRIS as a means of payment. Education, gender and age of merchants are aspects that can be researched deeper which are the determining factors for merchants using QRIS. The interview results show that QRIS is able to increase merchants' sales profits. There are several reasons why the respondents do not use QRIS, such as lack of understanding on how to use it, with 19.4%, consumers rarely use QRIS with 22.6%, inconvenience of using it with 22.6%, and making losses with 3.2%.